2008
DOI: 10.1177/1940161208319292
|View full text |Cite
|
Sign up to set email alerts
|

What's the Fuss About? The Interplay of Media Hypes and Politics

Abstract: Media hypes on social problems occur on a regular basis and they seem to generate a lot of political activity. This article asks the question whether media hypes have any influence on public policies central issue of the hype—and if any, what kind of influence? Five media hypes on the same subject area (the care for and spending on the elderly) are analyzed.Their immediate influence on policy making is traced, and although the media often is assumed to exercise real political power through media hypes, no—or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 13 publications
0
31
0
3
Order By: Relevance
“…Several studies have shown that political actors do not automatically react to media information as it becomes more salient, but mainly, or only, when this information fits their already existing issue agenda. So, the news not only provides useful information about topics and events, but offers a window of opportunity for some political actors to highlight their existing issue priorities (Elmelund‐Præstekær & Wien, ; Kingdon, ; Yanovitsky, ).…”
Section: The Information Functionmentioning
confidence: 99%
“…Several studies have shown that political actors do not automatically react to media information as it becomes more salient, but mainly, or only, when this information fits their already existing issue agenda. So, the news not only provides useful information about topics and events, but offers a window of opportunity for some political actors to highlight their existing issue priorities (Elmelund‐Præstekær & Wien, ; Kingdon, ; Yanovitsky, ).…”
Section: The Information Functionmentioning
confidence: 99%
“…Although media attention has not been studied as thoroughly as geographic proximity or political ideology, many scholars have speculated about the possible impact of media attention on the spread of policies and the decisions of policy makers (Elmelund-Praestekaer & Wien, 2008). Walker (1969) even suggested that media attention may negate some of the effects of geographic proximity that were described earlier in this section, since the media could allow states to learn about policies currently in place in faraway states.…”
Section: What Variables Affect the Diffusion Of Policies?mentioning
confidence: 96%
“…It is argued that while intense media coverage did not have an immediate influence on public policy, it did influence the government agenda by providing politicians with opportunities to talk about particular issues, including NH supervision. Moreover, the authors conclude that “a series of media hypes in the late 1990s ending (in 2000) was a driving force behind the decision to revise the national regulation in 2001” (Elmelund‐Præstekær & Wien, , p. 263). Although recurring intense media coverage might not have been sufficient to spur reform, it played a key role in priming the political process, making later change possible.…”
Section: Introductionmentioning
confidence: 99%